Shadow Sands - Bryndza, Robert (Seattle : Thomas & Mercer, 2020)
"Criminology academic Kate Marshall is on a scuba jaunt with her son when they dive toward a shocking discovery: the body of a teenage boy entangled below the surface of the Shadow Sands reservoir. The detective chief inspector's too-quick narrative of a tragic drowning doesn't add up, and when Kate follows the evidence, it leads to a darker discovery. The victim is only the latest in a series of mysterious deaths and disappearances linked to the moorlands--and a mythic phantom said to hide in the rolling fog. When a researcher of urban legends vanishes without a trace, Kate and her associate Tristan Harper must act fast and look deep if they hope to find her alive. But the elusive serial killer they're hunting isn't the only one a step ahead of Kate and Tristan. Someone else is making dead certain that the secrets of Shadow Sands stay buried."--Amazon.com
"Bestselling author of The Girl in the Ice"--Dust jacket.
Keywords: Women college teachers -- Fiction; Women detectives -- Fiction